Variasi metode hafalan al-qur’an berbasis diferensasi gaya belajar pada mahasiswa iat a uin maulana malik ibrahim malang - Alaikassalam, Mohammad (Maliki Interdisciplinary Journal, 2026)
In an increasingly rapid digital era, the tradition of memorizing the Qur’an faces new and complex challenges, particularly the emergence of various memorization methods, which are generally classified into three categories: the visual method (using printed mushaf), the auditory method (listening to murottal recitations), and the audio-visual method (reading the Qur’an while simultaneously listening to murottal recitations). This phenomenon directs the discussion toward examining the influence and relationship between students’ learning styles and the Qur’an memorization methods they choose.The purpose of this study is to enable students to clearly analyze which memorization method is most suitable for their dominant learning style. Using a qualitative descriptive approach, the research concludes that the relationship between students’ learning styles and Qur’an memorization methods is significant and mutually influential. Auditory learners tend to achieve better results with sound-based methods (murottal), visual learners with reading-based methods (printed mushaf), while audio-visual learners require a combination of both to strengthen and maintain long-term memorization. Furthermore, students of the IAT Class A at UIN Malang were found to predominantly prefer the visual method, namely memorizing by looking at the printed mushaf.